A multi-agent system approach for trustworthy cloud service discovery - Akinwunmi, Akinwale; Olajubu, emmmanuel (cogent OA, 2023)
TITLE:A multi-agent system approach for trustworthy cloud service discovery VOLUME NO:3 ISSUE NO:02 SEPTEMBER,2016 PAGES:17